Inequality and Trade Policy: Pro-Poor Bias of Contemporary Trade Restrictions - Beyza Ural Marchand (Institute of Labor Economics (IZA), 2019)
This paper studies the pro-poor bias of contemporary trade policy in India by estimating the household welfare effects of eliminating the current protection structure. The elimination of a pro-poor trade policy is expected to have lower welfare gains or higher welfare loss at the low end of the per capita expenditure distribution. The paper first constructs trade restrictiveness indices for household consumption items and industry affiliations using both tariffs and the ad-valorem equivalent of non-tariff barriers. The welfare effects are estimated through its impacts on household expenditure and earnings. The results indicate that Indian trade policy is regressive through the expenditure channel as it disproportionately raises the cost of consumption for poorer households, while it is progressive through the earnings channel in urban areas and neutral in rural areas. The net distributional effect through these two channels is estimated to be regressive, and elimination of current trade protection structure is expected to reduce inequality. These results indicate that a trade protection structure that designed as a progressive trade policy through the earnings channel may induce price effects that are regressive through the expenditure channel.
Keywords: D31; F14; I30; O12; 330; trade protection; consumption inequality; poverty